1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Very easy question

  1. Jul 22, 2011 #1
    Is it correct ?
    $ \sqrt{(-1)^2} $ = $ \sqrt{(-1)}\sqrt{(-1)} $= $ i*i $=$ i^2 $ =$ -1 $
    or
    $ \sqrt{(-1)^2} $ = $ \sqrt{(1)} $=1
     
  2. jcsd
  3. Jul 22, 2011 #2

    eumyang

    User Avatar
    Homework Helper

    You mean this?
    [itex]\text{1) }\sqrt{(-1)^2} = \sqrt{(-1)} \cdot \sqrt{(-1)} = i \cdot i = i^2 = -1[/itex]
    [itex]\text{2) }\sqrt{(-1)^2} = \sqrt{1} = 1[/itex]

    Note that the product property of radicals,
    [itex]\sqrt{ab} = \sqrt{a} \cdot \sqrt{b}[/itex]
    holds only if both a and b are non-negative.
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook